Intention towards whistle-blowing reporting among internal auditors - Md. Idris, Kamil; Danila, Raudah; Sharif, Zakiyah; Ali, Azharudin; Wan Ahmad, Wan Norhayati (Universiti Utara Malaysia, 2012)
The objective of this study is to determine the internal auditors’ readiness to be a whistleb-lower.For over 20 years, many researchers across the disciplines have done research that examined issues related to whistle-blowing but there have been limited research themes on the internal auditors as whistle-blowers being carried out.This study examined the relationship between organizational-professional conflict, social influence, self-efficacy, and intention towards whistle-blowing.In doing so, the study also explored two aspects of moderating interaction of moral obligation and awareness.This study utilized the Theory of Planned Behavior model as a research framework as it is widely accepted as a general framework for predicting behavioral intentions.This study applied the method of random sampling based on list given by the Institute of Internal Auditors Malaysia (IIAM).The questionnaires were distributed to auditors by mail.A total of 115 auditors participated in this study.This research provides evidence that the auditors with professional conflict awareness will have higher intention towards whistle-blowing.The findings also indicate that there are moderating effects of organizational moral obligation in the relationship between organizational conflict and intention towards whistle-blowing reporting.Specifically, the results indicate that with low level of moral obligation, auditors are more likely and have more intention to blow the whistle in the presence of fraud or wrongdoing in the organization. Finally, auditors who have high level of self-awareness will have high intention towards whistle-blowing reporting when dealing with professional conflict.As a conclusion, based on the analysis, auditors who experience professional conflict, social influence and self-efficacy (without being influenced by the moderator) will only intend towards whistle-blowing reporting if deemed necessary.In addition, auditors who encounter professional conflict and at the same time have high level of statutory moral obligation and self-awareness will have higher intention towards whistle-blowing reporting.